Neonatal Marfan syndrome caused by an exon 25 mutation of the fibrillin-1 gene - (:unkn) unknown (My University, 2004)
Neonatal Marfan syndrome caused by an exon 25 mutation of the Fibrillin-1 gene: We describe a male infant with severe arachnodactyly, hypermobility of the fingers, flexion contractures of elbows, wrists, hips, and knees, microretrognathia, crumpled ears, rockerbottom feet, loose redundant skin, and lens dislocations. Cardiac valve insufficiency and aortic dilatation resulted in cardiac failure, decompensated with digitalisation and death occurred at the age of 4 months. This case represents the severe end of the clinical spectrum of Marfan syndrome, namely neonatal Marfan syndrome. Molecular diagnostic analyses confirmed a de novo exon 25 mutation in the FBN1 gene.
Keywords: Humans; Male; Abnormalities, Multiple; Infant, Newborn; Fatal Outcome; Ectopia Lentis; Fibrillin-1; Fibrillins; Marfan Syndrome; Microfilament Proteins; Mutation, Missense